(untitled) (Revista de História da UEG (REVHIST), 2020)
Abstract: This article is the result of research linked to the doctorate that is under development, whose theme is recorded in the embryo analysis of the multiple mystical representations of Brasilia. The thematic clipping offers a debate on the presence of religious buildings in Oscar Niemeyer’s modernist project. Although a new capital has modern and futuristic characteristics, we realize that this type of modernity does not cause a distancing of religious factor. Theoretically, it discusses with authors from the religious and social sciences, which describe the contemporary religious phenomenon, among which we highlight Mircea Eliade and Peter Berger. This debate is aimed at the twists, or negotiations, that contemporary societies have been perfecting in the face of new spiritualist demands. Keywords: Brasília. Modernism. Religiosity. Oscar Niemeyer.